2015
DOI: 10.1371/journal.pone.0136254
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and Evolutionary Dynamics of Influenza B Viruses in Malaysia, 2012-2014

Abstract: Epidemiological and evolutionary dynamics of influenza B Victoria and Yamagata lineages remained poorly understood in the tropical Southeast Asia region, despite causing seasonal outbreaks worldwide. From 2012–2014, nasopharyngeal swab samples collected from outpatients experiencing acute upper respiratory tract infection symptoms in Kuala Lumpur, Malaysia, were screened for influenza viruses using a multiplex RT-PCR assay. Among 2,010/3,935 (51.1%) patients infected with at least one respiratory virus, 287 (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 58 publications
6
29
2
Order By: Relevance
“…In North America, studies have reported rates of (3.11–12.50) x 10 −3 [52] and 5.41 x 10 −3 [53]. For influenza B viruses, the nucleotide substitution rate of the NA gene in the present study is comparable to those reported in Australia and New Zealand (mean nucleotide substitution rate of 2.04 × 10 −3 substitutions/site/year for the Victoria lineage and 2.25 × 10 −3 substitutions/site/year for the Yamagata lineage) [54] and Malaysia (2.5–3.4 x 10 −3 ) [55]. In contrast, the mean nucleotide substitution rate of the NA gene of A(H1N1)pdm09 in the present study was slightly lower than a previous study of 5.21 × 10 −3 substitutions/site/year [3] and 5.27 x 10 −3 [56], which may be attributed to the study sample size and sequence diversity of the strains.…”
Section: Discussionsupporting
confidence: 83%
“…In North America, studies have reported rates of (3.11–12.50) x 10 −3 [52] and 5.41 x 10 −3 [53]. For influenza B viruses, the nucleotide substitution rate of the NA gene in the present study is comparable to those reported in Australia and New Zealand (mean nucleotide substitution rate of 2.04 × 10 −3 substitutions/site/year for the Victoria lineage and 2.25 × 10 −3 substitutions/site/year for the Yamagata lineage) [54] and Malaysia (2.5–3.4 x 10 −3 ) [55]. In contrast, the mean nucleotide substitution rate of the NA gene of A(H1N1)pdm09 in the present study was slightly lower than a previous study of 5.21 × 10 −3 substitutions/site/year [3] and 5.27 x 10 −3 [56], which may be attributed to the study sample size and sequence diversity of the strains.…”
Section: Discussionsupporting
confidence: 83%
“…All sIBVs carry V124A substitution in the 120‐loop, which has been also found in one of Italian IBVs (B/Milano/35CA/2016) . I146V substitution in the 150‐loop of all sIBVs has been also observed in 89.6% of B/Victoria clade 1 strains isolated in Italy during the period 2010‐15, several influenza B‐Victoria lineage viruses isolated in Cambodia in 2010‐11 as well as 67 Victoria‐1 viruses isolated in Malaysia, 2012‐14 . None of Amino acid substitutions in the 160‐loop were found in all sIBVs.…”
Section: Discussionmentioning
confidence: 82%
“…In the analysis of variable importance, we also checked weather conditions, which could influence influenza virus transmission (15)(16)(17). The weather conditions, including the weekly average temperature, humidity, wind speed, and maximum temperature, seemed insignificant for predication because their influence could be implied by the history observations.…”
Section: Discussionmentioning
confidence: 99%